2016
DOI: 10.3389/fnmol.2016.00123
|View full text |Cite
|
Sign up to set email alerts
|

Novel Non-phosphorylated Serine 9/21 GSK3β/α Antibodies: Expanding the Tools for Studying GSK3 Regulation

Abstract: Glycogen synthase kinase 3 (GSK3) β and α are serine/threonine kinases involved in many biological processes. A primary mechanism of GSK3 activity regulation is phosphorylation of N-terminal serine (S) residues (S9 in GSK3β, S21 in GSK3α). Phosphorylation is inhibitory to GSK3 kinase activity because the phosphorylated N-terminus acts as a competitive inhibitor for primed substrates. Despite widespread interest in GSK3 across most fields of biology, the research community does not have reagents that specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…Immunoblots were developed using a well-characterized antibody that selectively recognizes active GSK3β species dephosphorylated at the regulatory serine 9 residue (anti-dpS9-GSK3β; Figure 4 ). Dephosphorylation of this critical regulatory residue in GSK3β by any of several protein phosphatases, including PP1, represents a major activation mechanism for this kinase (Grabinski and Kanaan, 2016 ). A phosphorylation-independent antibody against GSK3β provided an internal protein loading control (anti-Total GSK3β).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblots were developed using a well-characterized antibody that selectively recognizes active GSK3β species dephosphorylated at the regulatory serine 9 residue (anti-dpS9-GSK3β; Figure 4 ). Dephosphorylation of this critical regulatory residue in GSK3β by any of several protein phosphatases, including PP1, represents a major activation mechanism for this kinase (Grabinski and Kanaan, 2016 ). A phosphorylation-independent antibody against GSK3β provided an internal protein loading control (anti-Total GSK3β).…”
Section: Resultsmentioning
confidence: 99%
“…The following antibodies were used for Western blots: KHC (H2 clone; Pfister et al, 1989 ); Total GSK3 (Cell Signaling Technology #D75D3); pJNK (Cell Signaling Technology #9251). Anti-dp-ser9/21-GSK3α/β (clone 15C2; Grabinski and Kanaan, 2016 ) and anti-tau (clone TNT1) were provided by Dr. Nicholas Kanaan (Michigan State University).…”
Section: Methodsmentioning
confidence: 99%
“…However, it has also been noted that Ser9 phosphorylation is not an accurate indicator of GSK3β activity, and a method for properly measuring GSK3β activity in vivo has long been expected. Recently, the antibodies recognizing non-phosphorylated Ser9 were reported 36 . Here, we developed a method for estimating the kinase activity of GSK3β using Phos-tag SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%
“…Extending these findings, other kinases were found to regulate AT indirectly by modulating localized GSK3 activation (Morfini et al, 2004; Ratner et al, 1998). Unlike most protein kinases, GSK3 activation requires dephosposphorylation of an inhibitory phosphorylation site (Grabinski and Kanaan, 2016). Interestingly, it was found that inhibition of the major protein kinase CDK5 promotes activation of axonal protein phosphatase 1 (PP1), which in turn dephosphorylated and activated GSK3 (Morfini et al, 2004; Ratner et al, 1998).…”
Section: Introductionmentioning
confidence: 99%